Why Old Places Matter : How Historic Places Affect Our Identity and Well-Being. - Mayes, Thompson M. (American Association for State and Local History, 2018)
This book explores the reasons that old places matter to people such as the feelings of belonging, continuity, stability, identity and memory, as well as the more traditional reasons, such as history, national identity, and architecture. This book brings these ideas together in evocative language and with illustrative images.